Bodily autonomy and trauma: understanding the nature of the association between sexual trauma, an external locus of control, and depressive symptoms - Thomas, Johanna M. (Violence and victims, 2024)
There is growing evidence suggesting an increased perception of control is associated with reduced psychological distress among survivors of sexual trauma. The current study advances the extant literature by investigating the association between depressive symptoms, sexual trauma, and an external locus of control or the perception life events are outside one’s own control. To do so, we analyze data from the New Family Structures Study, a nationally representative survey of U.S. adults ages 18-39. Results from ordinary least square regression analyses suggest sexual trauma and an external locus of control are associated with significantly greater depressive symptoms and that external control exacerbates the association between sexual trauma and depression. Such findings suggest future research should investigate environmental control for sexual trauma survivors in areas such as prenatal care and the justice system.